40.5k views
0 votes
Find the value of below algebriac expression for x=2,y=-1 and z=2 i. 4x2−3y2+5z24x2−3y2+5z2 ii. 3x3−2x(4yz+5x2)3x3−2x(4yz+5x2) iii. 1−4x(yz+3xy)1−4x(yz+3xy)

1 Answer

2 votes

Answer:

i. 33

ii. 1488

iii. 65

Explanation:

i. 4x² − 3y² + 5z²

Putting the values x=2, y=-1 and z=2

4(2)² − 3(-1)² + 5(2)²

4×4 − 3×(1)² + 5×(4)

(16) - (3×1) + (20)

16 - 3+ 20

36 - 3

33

ii. 3x³ − 2x(4yz+5x²)

Putting the values x=2, y=-1 and z=2

[3(2)³ − 2×2(4×(-1)×2 + 5×(2)²)]

[3(8)³ − 2×2(-8 + 5×4)]

[3 ×512 - 2×2(-8 +20)]

[1536 - 4(12)]

[1536 - 48]

1488

iii. 1−4x(yz+3xy)

Putting the values x=2, y=-1 and z=2

[1 - 4 × 2((-1)×2 + 3×2×(-1))]

[1- 8(-2 + (-6))]

[1- 8 (-2 -6)]

[1 - 8(-8)]

[1 +64]

65

User SignalRichard
by
5.8k points